2004
DOI: 10.1189/jlb.0703320
|View full text |Cite
|
Sign up to set email alerts
|

GRK6 deficiency is associated with enhanced CXCR4-mediated neutrophil chemotaxis in vitro and impaired responsiveness to G-CSF in vivo

Abstract: The stromal cell-derived factor-1 (SDF-1)/CXC chemokine receptor 4 (CXCR4) signaling pathway is thought to play an important role in the induction of neutrophil mobilization from the bone marrow in response to granulocyte-colony stimulating factor (G-CSF) treatment. CXCR4 belongs to the family of G protein-coupled receptors. Multiple members of this receptor family are desensitized by agonist-induced G protein-coupled receptor kinase (GRK)-mediated phosphorylation. Here, we demonstrate that in vitro SDF-1-indu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
63
0
1

Year Published

2006
2006
2019
2019

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 82 publications
(65 citation statements)
references
References 53 publications
(53 reference statements)
1
63
0
1
Order By: Relevance
“…14). However, to date, the GRKs responsible for agonist-promoted phosphorylation, desensitization, and/ or endocytosis of CXCR4 remain to be characterized, although some alterations of CXCR4 functions have been revealed in mice lacking Grk6 (10,15). In this work, we identify GRK3 as a key regulator of CXCR4 attenuation, the impaired activity of which in WHIM WT cells accounts for the enhancement of CXCR4-mediated G protein-dependent responses.…”
Section: Introductionmentioning
confidence: 88%
See 1 more Smart Citation
“…14). However, to date, the GRKs responsible for agonist-promoted phosphorylation, desensitization, and/ or endocytosis of CXCR4 remain to be characterized, although some alterations of CXCR4 functions have been revealed in mice lacking Grk6 (10,15). In this work, we identify GRK3 as a key regulator of CXCR4 attenuation, the impaired activity of which in WHIM WT cells accounts for the enhancement of CXCR4-mediated G protein-dependent responses.…”
Section: Introductionmentioning
confidence: 88%
“…Recent findings indicate that different GRKs may set in motion distinct functions of GPCR-bound β-arrestin (26,27,37,38), opening the possibility that a specialization of GRKs also takes place in the regulation of β-arrestin2-dependent CXCR4 signaling. For instance, studies from Grk6-deficient mice suggest a positive contribution of this kinase to the CXCL12-induced chemotaxis of T cells, whereas Grk6 appears to play an opposite role in neutrophils (10,15). These results, if extended to the regulation of CXCR4-mediated signaling in human cells, would open the possibility that GRK6 and GRK3 differentially regulate CXCR4 activities.…”
Section: Figurementioning
confidence: 97%
“…1). CXCL12 activation of CXCR4 desensitizes CXCR4 though GRKmediated receptor phosphorylation and β-arrestin binding (Cheng ZJ et al, 2000;Fong AM et al, 2002;Vroon A, 2004). β-Arrestin2 enhances CXCR4-mediated activation of p38 MAPK that is critically involved in CXCR4-mediated chemotaxis (Sun Y, et al, 2002).…”
Section: Cxcl12/cxcr4 Signaling Pathwaysmentioning
confidence: 99%
“…Although most of the substrates of GRK6 are probably still unknown, it has been shown that GRK6 regulates desensitization of the chemokine receptor CXCR4, the BLT1 receptor for the leukotriene B4 (LTB4) and the calcitonin gene-related peptide (CGRP) receptor (13)(14)(15)(16). Furthermore, GRK6 binds and phosphorylates PDZ domains in Na + /H + exchanger regulatory factor (NHERF) and binds to downstream regulatory element antagonistic modulator (DREAM), both regulators of ion channels, indicating that GRK6 can also regulate cellular signaling via mechanisms independent of GPCR desensitization (17,18).…”
Section: Introductionmentioning
confidence: 99%